Disclosing Unwanted Pursuit Victimization: Indirect Effects of Negative Reactions on PTSD Symptomatology Among Undergraduate Women - Dardis, Christina M. (Journal of interpersonal violence, 2021)
A growing literature has documented that negative social reactions to disclosures of sexual and intimate partner violence (IPV), such as victim blaming or disbelief, can negatively affect survivors’ recovery. However, despite growing recognition of the frequency of unwanted pursuit behaviors (UPBs; for example, stalking, excessive or threatening contact) following romantic relationships and their negative effects on survivors, research to date has not explored disclosures, social reactions, or their impacts among victims of UPBs. The purpose of the present study was to assess the frequency of disclosures of UPB victimization to various sources, social reactions received, and their associations with symptoms of posttraumatic stress disorder (PTSD). Among a sample of 318 undergraduate women (ages 18-24) who reported a breakup within the past 3 years, 59.7% (n =190) reported experiencing UPBs. Nearly all of the women (92.6%; n =176) who experienced UPBs disclosed their victimization to others. Among women who disclosed, the most frequent recipient of disclosure was a female friend (93.2%, n = 164) and women reported receiving higher mean positive than negative social reactions (p < .001). Results supported the hypothesized indirect effect of UPB victimization on PTSD symptoms through increases in negative social reactions (p < .001); these results suggest that negative social reactions to UPB victimization may increase the risk for PTSD symptomatology. By contrast, there was no indirect effect via positive social reactions (p = .205). Implications for research and clinical practice will be discussed.